Transcriptomic evaluation of plant growth inhibitory activity of goniothalamin from the Malaysian medicinal plant goniothalamus andersonii - Wasano, Naoya; Takemura, Tomoko; Ismil, Raihan; Bakar, Baki; Fujii, Yoshiharu (SAGE Publications, 2015)
Goniothalamin produced by the Malaysian medicinal plant, Goniothalamus andersonii J. Sinclair, strongly inhibits plant growth. However, its mode of action has not been characterized at the gene expression level. We conducted DNA microarray assay to analyze the changes in early gene responses of Arabidopsis thaliana seedlings. After a 6-h exposure to goniothalamin, we observed an upregulation of genes highly associated with heat response, and 22 heat shock protein (AtHSP) genes were upregulated more than 50 fold. Together with these genes, we observed upregulation of the genes related to oxidative stress and protein folding. Also, the genes related to cell wall modification and cell growth, expansin (AtEXPA) genes, were significantly downregulated. The results suggested that goniothalamin induces oxidative stresses and inhibits the expression of cell wall-associated proteins resulting in growth inhibition of Arabidopsis seedlings.